Dextropropoxyphene induced hepatotoxicity: a report of nine cases. - Rosenberg, WM; Ryley, N; Trowell, J; McGee, J; Chapman, R (1993)
Nine patients are described with jaundice, upper abdominal pain and malaise attributable to dextropropoxyphene hepatotoxicity. In each case the history was suggestive of large bile duct obstruction. All patients underwent ultrasound examination and percutaneous liver biopsy. Three patients also underwent endoscopic retrograde cholangio pancreatography. The histological features of the biopsies concur with previously reported cases of dextropropoxyphene hepatotoxicity. The histological changes seen on biopsy were remarkably constant, consisting of centrilobular cholestasis, portal tract inflammation and bile duct abnormalities, in all cases mimicking large bile duct obstruction. Fifteen previous patients with probable dextropropoxyphene hepatotoxicity have been described. The occurrence of 9 further cases at one centre, 6 presenting within 12 months, suggests that it is much more common than previously assumed and may be misdiagnosed as large bile duct obstruction.